3x-(x+26)=180

Simple and best practice solution for 3x-(x+26)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(x+26)=180 equation:


Simplifying
3x + -1(x + 26) = 180

Reorder the terms:
3x + -1(26 + x) = 180
3x + (26 * -1 + x * -1) = 180
3x + (-26 + -1x) = 180

Reorder the terms:
-26 + 3x + -1x = 180

Combine like terms: 3x + -1x = 2x
-26 + 2x = 180

Solving
-26 + 2x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + 2x = 180 + 26

Combine like terms: -26 + 26 = 0
0 + 2x = 180 + 26
2x = 180 + 26

Combine like terms: 180 + 26 = 206
2x = 206

Divide each side by '2'.
x = 103

Simplifying
x = 103

See similar equations:

| 5y-10=40 | | 4w-8w=28 | | 2x+(x-33)=90 | | -4=7x+1-8 | | 4(x-5)=x+4 | | 11n=10+16 | | 4x+(x+35)=90 | | (3x/(x-7))-((x+7)/x)=0 | | (3x/(x-7))-((x+7)/x) | | x-3=(5x-1)^1/2 | | 7g=6 | | 700-2x=50+2x | | -49.95-20x= | | x^2+4x-y=7 | | V=x(14-2x)(10-2x) | | 5(2x-7)=3(4x+9) | | 2x/5=x+6 | | 7m-3=3m+17 | | 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 | | 9x+13=2x+174 | | t^3-5t^2+4t=0 | | -8+2x=-16 | | 12-7x=69-28x | | -4.9x^2+22t+42=0 | | 47+0.5x= | | -3-x=-1 | | 3+2x=-11 | | -5x-7=48 | | 1-4x=-11 | | 9(X-2)*2(2X-1)=8 |

Equations solver categories